Achievements economic efficiency of machinebuilding enterprise based on indicators competitiveness of its products - Siketina, Natalya Hennadievna (Yunona Publishing, 2018)
The non-price factor in the process of assessing the level of petitiveness of products is practically not used, therefore its level, calculated without its consideration, does not objectively reflect the specific situation on the market. Summing up outlined above conclude that the use of the non-price and logistic approach as factors of increasing the competitiveness of products implies that decisions taken in relation to purchasing, transportation and storage of products should also be considered from their influence on the formation of costs and profits of the enterprise. The proposed approach for calculating non-price and logistic factors ensuring the competitiveness of products will provide a more accurate assessment he level of competitiveness of domestic products by accounting for expenses associated with the movement of goods. Work in this direction is promising, especially for products sold on the foreign market.
Keywords: business strategy; competitiveness; non-price competitiveness; product; logistic factor